SOSIALISASI STRATEGI PEMASARAN DALAM RANGKA OPTIMALISASI KEUNTUNGAN UMKM KECAMATAN RANCABUNGUR MELALUI PERLUASAN PASAR DI DUNIA DIGITAL - Prisca Nurmala Sari; Fadly; Dian Andrayani; Adi Nurhadi; Mas Fierna Janvierna (Jurnal Abdimas Ilmiah Citra Bakti, 2023)
The growth of MSMEs is very decisive and contributes to Indonesia's economic growth. The Indonesian government must support the development of Indonesian MSMEs. MSMEs are strong to economic shocks but if they are not supported and assisted, MSMEs will collapse. MSMEs are must be going digital, especially in marketing and sales of MSME products. MSMEs must be able to compete with other competitors, especially the imported products. Rancabungur District is one of the subdistricts in Bogor Regency which has a lot of potential resources to be developed. The problem faced by MSME actor is a marketing problem that has not been going digital. Based on this problem, the activity of online marketing strategy socialization needs to be conducted as an early stage of mentoring MSMEs in Rancabungur District. This program is conducted using the explanation and discussion method. This activity began with giving pre-test and post-test. Judging from the results of the questionnaires which had been distributed, almost a half more, the participants of this program were aged 37-47 years old, female, worked as entrepreneurs, and produced any kinds of food. Judging from the implementation of digital marketing by MSME participants, around 69% of participants already have a brand; 59% have labels ; 97% have their own packaging; and 56% of participants have attached the brand and label on their packaging. From all the participants in this program, only 8% who have not implemented the digital marketing, while the rest have implemented the digital marketing eventhough only through one social media. The social media used by the participants are WhatsApp, Facebook, Instagram, and others. There are also MSME participants who sold their products through e-commerce as much as 10%. As much as 13% of MSME participants use online taxibike services (ojol). By conducting this socialization activity, it can be seen that the level of interest and knowledge of digital marketing for MSMEs in Rancabungur District has increased.